2007
DOI: 10.1080/10253890601135426
|View full text |Cite
|
Sign up to set email alerts
|

Differential vascular adaptive response to stress exposure in male and female rats: Role of gonadal hormones and endothelial cells

Abstract: Stress-induced vascular adaptive responses show gender differences. The magnitude of the adaptive response is dependent on testicular hormones and involves endothelial nitric oxide-system hyperactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…In the present study, we found no differences in VR between vehicle-treated young males and females. This response is in agreement with previous reports (Júnior and Cordellini, 2007 ; Loria et al, 2014 ).…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, we found no differences in VR between vehicle-treated young males and females. This response is in agreement with previous reports (Júnior and Cordellini, 2007 ; Loria et al, 2014 ).…”
Section: Discussionsupporting
confidence: 94%
“…Stress, in acute or chronic models, improves vascular function to different agonists 7 , 14 , 16 , 25 . Our results corroborate these data, in which increased responses to noradrenaline and acetylcholine were observed.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate previous reports showing that stress promotes endothelial dysfunction 2,3,19,20 . However, other studies reported that exposure to stress may actually enhance, rather than impair, endothelial function 1,21,22 .…”
Section: Discussionmentioning
confidence: 95%